The Pattern of Relationships Between School Context, Teachers’ Characteristics and Performances, and School Principals’ Conflict Resolution Styles and School Happiness - Ersöz ALKAN; Mustafa ÖZGENEL (Hayef: Journal of Education)
The aim of this research is to determine whether the school context, teacher characteristcs, and school principals’ confict management styles predict teachers’ performance and perceptons of school happiness. The research was carried out according to the relatonal survey model. The study group for the research consists of 410 teachers working in public schools in Istanbul. Informaton Form, “Rahim Organizatonal Confict Questonnaire II,” “School Happiness Scale,” and “Teacher Performance Evaluaton Scale” were used as data collecton tools. Data were analyzed using correlaton and multple regression analysis. According to the fndings, while the number of teachers in the school afects school happiness negatvely, the school principals’ integratng and compromising confict resoluton styles afect school happiness positvely. In additon, school happiness and school principals’ conciliatory confict resoluton style increase teachers’ performance by positvely afectng them. It has been revealed that the school principals’ accommodatng style of confict resoluton is a common variable that predicts school happiness and teacher performance.